Influence of Bake Hardening on Plastic Strain Dependency of Elastic Modulus - Kusaka Shota; Iwama Takashi; Sato Kentaro; Ohnishi Yoichiro; Shiozaki Tsuyoshi; Yoshida Fusahito (MATEC Web of Conferences)
Bake hardening (BH) steel sheets are widely used for automotive outer panels because of their high performance of dent resistance. BH is a process that induces a remarkable yield stress increase by strain ageing in paint baking process after press forming. To understand the BH effect on the dent resistance, the full process of forming/springback, BH and the dent-deformation/springback should be examined. BH behaviors of two types steel, TS340BH and TS440BH, were investigated by performing uniaxial tension, compression and bending experiments for tensile pre-strained BH specimens. The yield-point phenomenon appeared in tension of the BH specimens, but it was not observed in compression after BH although the flow stress increased by BH. The elastic modulus significantly affects the prediction accuracy of springback. However, the impact of BH on the plastic-strain-dependent elastic modulus has not been clarified. The evaluation of the relationship between the elastic modulus and BH provided the following key findings: the elastic modulus decreased with increasing plastic strain, however, it completely recovered to initial Young's modulus by BH. This BH-induced elastic modulus recovery is described by the modified Yoshida-Uemori (Y-U) elastic model (BH Y-U model). The BH bending behaviors directly correspond to the tensioncompression BH characteristics.